TI_GERICHTE 12.2015.24 vom 2. März 2016 , Banca - reponsabilità per gestore esterno - onere di quantificazione della domanda - TI Tribunale d'appello (2016)
Banca - reponsabilità per gestore esterno - onere di quantificazione della domanda